Malaysian Academician Stress Index: Construct Validity and Reliability Using RASCH Model Approach - Khairunesa Isa; Wan Hanim Nadrah Wan Muda; Laily Paim; Khadijah Alavi; Jalihah Md Shah; Nor Aisah Jamil (Psychology and Education, 2021)
Stress can have an impact on academics performance in the workforce.This study aimed to generate empirical evidence on validity and reliability of the items of Malaysian Academician Happiness Index (MAHI) using Rasch Model by Winstep software version 3.69.1.11. The construct validity was examined by analysing the point-measure correlation index (PTMEA), infit and outfit MNSQ values; a survey technique was used in this preliminary study as the major method on the MAHI instrument on 30 academic leader 's at one of the Malaysian public universities. The result showed that the reliability of MAHI instrument item was 0.76 which is accepted to the real study. Statistical data implied that out of 100 items, 28 items or 28% of the instrument got index value less than 0.3 which were suggested to be omitted or reviewed. However, these items can be maintained by consulting the expert. This study is hoped to bring a new holistic dimension on the academic stress measurement index that can help university management to develop a program to reduce stress and improve the quality of academician's life.